Mixed and Ambiguous Endometrial Carcinomas: A Heterogenous Group of Tumors With Different Clinicopathologic and Molecular Genetic Features. (July 2016) - Espinosa, Iñigo; D'Angelo, Emanuela; Palacios, José; Prat, Jaime
Abstract : Besides endometrioid, serous, and clear cell carcinomas, there are endometrial carcinomas exhibiting mixed and ambiguous morphologic features. We have analyzed the immunophenotype (p53, p16, β-catenin, ER, HNF-1B, MLH1, and Ki-67) and mutational status ( PTEN, KRAS, PIK3CA, and POLE ) of 7 mixed carcinomas and 13 ambiguous carcinomas, all of them classified initially as mixed carcinomas. Only 2 of the 7 (28%) mixed carcinomas showed different immunophenotypes in different components. All but 2 tumors (5/7, 71%) overexpressed p53 and p16 and were negative for ER. Both carcinomas (2/7, 28%) showed a prominent micropapillary component that resembled an ovarian low-grade serous carcinoma and merged with villoglandular endometrioid carcinoma. The ambiguous carcinomas exhibited glandular architecture, high nuclear grade, and overlapping features of endometrioid and serous carcinomas. All tumors overexpressed p53 and p16, and the majority of cases (12/13, 92%) were negative for ER. KRAS mutations were identified in 3 of 7 (42%) mixed carcinomas, including the 2 cases with a "low-grade" serous–like component. PIK3CA mutations occurred in 2 (2/13, 15%) ambiguous carcinomas and PTEN mutations in 1 (1/7, 14%) mixed and 1 (1/13, 8%) ambiguous carcinoma. POLE exonuclease domain mutations were encountered in a case of mixed undifferentiated and well-differentiated (dedifferentiated) carcinoma. Two of the 7 (29%) mixed endometrial carcinomas and 5 of the 13 (38%) ambiguous carcinomas had extended beyond the pelvis (stages III and IV). Two of the 7 (29%) patients with mixed endometrial carcinoma and 6 of 12 (50%) patients with ambiguous endometrial carcinoma were alive with disease or had died of tumor. Our results show that, biologically, many so-called mixed carcinomas represent serous carcinomas with ambiguous morphology. Our series include 2 true mixed endometrial carcinomas with a "low-grade serous"–like component, microcystic, elongated, or fragmented features, KRAS mutations, and aggressive behavior.